2017
DOI: 10.1177/1081286517726371
|View full text |Cite
|
Sign up to set email alerts
|

Solvability and microlocal analysis of the fractional Eringen wave equation

Abstract: We discuss unique existence and microlocal regularity properties of Sobolev space solutions to the fractional Eringen wave equation, initially given in the form of a system of equations in which the classical non-local Eringen constitutive equation is generalized by employing spacefractional derivatives. Numerical examples illustrate the shape of solutions in dependence of the order of the space-fractional derivative.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
2
3
0
Order By: Relevance
“…In particular, it is found that both solid-like and fluid-like materials can have either infinite or finite wave speed. Singularity propagation properties of the memory and non-local type fractional wave equations are investigated in [17,18] using the tools of microlocal analysis, supporting the results obtained in [20].…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…In particular, it is found that both solid-like and fluid-like materials can have either infinite or finite wave speed. Singularity propagation properties of the memory and non-local type fractional wave equations are investigated in [17,18] using the tools of microlocal analysis, supporting the results obtained in [20].…”
Section: Introductionsupporting
confidence: 67%
“…In particular, it is found that both solid-like and fluid-like materials can have either infinite or finite wave speed. Singularity propagation properties of the memory and non-local type fractional wave equations are investigated in [17,18] using the tools of microlocal analysis, supporting the results obtained in [20]. Wave propagation phenomena in viscoelastic bodies, modeled by integer and fractional order models, including the question of wave speed and energy dissipation properties are analyzed in [8,9].…”
Section: Introductionsupporting
confidence: 56%
“…Generalizing the integer-order Eringen stress gradient non-local constitutive law, the fractional Eringen model (1.7) is postulated in [12], where the optimal values of the non-locality parameter and order of fractional differentiation are obtained with respect to the Born-Kármán model of lattice dynamics. Furthermore, wave propagation, as well as propagation of singularities, in nonlocal material described by the fractional Eringen model (1.7) is analysed in [13].…”
Section: Introductionmentioning
confidence: 99%
“…obtained by the Laplace transform inversion in (22) 1 and three expressed in terms of creep compliance…”
Section: Modelmentioning
confidence: 99%
“…Generalizing the integer-order Eringen stress gradient non-local constitutive law, the fractional Eringen model ( 7) is postulated in [11], where the optimal values of non-locality parameter and order of fractional differentiation are obtained with respect to the Born-Kármán model of lattice dynamics. Further, wave propagation, as well as propagation of singularities, in non-local material described by the fractional Eringen model ( 7) is analyzed in [22].…”
Section: Introductionmentioning
confidence: 99%